Physical activity and cardiovascular health indicators during early childhood - Proudfoot, Nicole A. (My University, 2020)
Cardiovascular disease begins to develop in childhood. Physical activity positively impacts cardiovascular health and lowers cardiovascular disease risk in school-aged children and adults; however, there is insufficient evidence to determine the effects of physical activity on cardiovascular health during early childhood. The specific dose of physical activity required for favourable cardiovascular health in this age group is also unknown. The purpose of this thesis was to explore the relationships between physical activity and cardiovascular health indicators during early childhood. In the first study, we found that physical activity engagement has beneficial effects on cardiovascular fitness, blood pressure, autonomic function, and arterial stiffness during early childhood. We then determined in the second study that to avoid unfavourable cardiovascular health, preschool-aged children should engage in at least 240 minutes of activity at any intensity, 80 minutes of moderate-to-vigorous physical activity, or 8700 steps per day. Finally, in the third study we evaluated a novel technique for examining arterial wall properties, carotid artery longitudinal wall motion, and determined that it was weakly associated with an established indicator of arterial stiffness (pulse wave velocity) in early childhood. These findings highlight that the benefits of physical activity on cardiovascular health begin in early childhood and the minimal amount of activity to avoid unfavourable cardiovascular health is higher than current recommendations. For the most part, physical activity benefited boys and girls similarly, although it is unclear if the physical activity targets apply equally to boys. We also determined that carotid artery longitudinal wall motion may not be an indicator of arterial stiffness in young children. Future studies should determine if the favourable effects of physical activity on cardiovascular health during early childhood carry over to later years and if achieving the physical activity targets determined in this thesis are associated with additional health benefits.
Physical activity and cardiovascular health in preschoolers
Keywords: child; physical activity; preschooler; accelerometry; cardiovascular health; vascular stiffness; fitness; blood pressure; heart rate; autonomic function; primordial prevention; guidelines; arterial wall motion